Design and construction of a permeation measurement equipment - Jareman, Fredrik (1999)
This project started due to the need for a permeation test facility at the division of chemical technology at Luleå University of technology. The project covers design, equipment selection and construction of the test facility. A permeation measurement testing system was constructed consisting of several components, which is capable of making advanced measurements of the permeation characteristics on different gases and liquids. The system will be automated by a computer system once routine tests are started. The system contains three main components: one gas chromatograph one tubular split type furnace and a heated zone. The heated zone contains evaporating units and pressure regulating equipment. Quantitative gas analysis of the retentate and permeate will be performed with the gas chromatograph, in order to evaluate separation characteristics of the membrane. Several limitations had to be made regarding temperature, pressure and other operating parameters in order to find appropriate equipment and keep costs manageable. Within these limitations, all equipment was ordered and mounted together into the permeation test facility. Validerat; 20101217 (root)